1999
DOI: 10.1023/a:1026654200916
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The diagnosis of adenocarcinoid (mucinous/goblet cell carcinoid) is usually unexpected by both clinicians and pathologists. We report here the case of a 74-year-old man with gastric lymphoma (B-cell MALToma) diagnosed by endoscopy, who was found on exploratory laparotomy also to have extensive intraabdominal involvement by adenocarcinoid, arising from the ileum and/or appendix. The patient died two years after diagnosis with bladder outlet and small bowel obstruction due to diffuse metastases. In addition to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Finally, 76 articles that contained interpretable data and fulfilled the eligibility criteria were included (Fig 1). [1690] In 16 articles the data extraction was made from its abstract [21,22,24,3335,37,45,64,70,71,73,74,80]. The flowchart for systematic literature review and articles included in the analysis is shown in Fig 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 76 articles that contained interpretable data and fulfilled the eligibility criteria were included (Fig 1). [1690] In 16 articles the data extraction was made from its abstract [21,22,24,3335,37,45,64,70,71,73,74,80]. The flowchart for systematic literature review and articles included in the analysis is shown in Fig 1.…”
Section: Resultsmentioning
confidence: 99%